Sex hormone profiles in men with migraine: a cross-sectional, matched cohort study - Triller, Paul; Storch, Elisabeth; Overeem, Lucas H.; Fitzek, Mira P.; Hoehne, Carolin L.; Terhart, Maria; Lange, Kristin S.; Reuter, Uwe; Raffaelli, Bianca (Frontiers in Neurology, 2025)
ObjectiveSex hormones play a key role in migraine pathophysiology, yet their impact in men remains unclear. This study investigates sex hormone profiles and their potential relationship with Calcitonin Gene-Related Peptide (CGRP) in men with episodic migraine.MethodsWe analyzed serum blood levels of sex hormones testosterone, estradiol (E2), progesterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH) and CGRP in age and body mass index (BMI)-matched men with and without migraine.ResultsA total of 120 male participants (n = 60 with migraine and n = 60 without migraine) completed the study. The mean age was 44.4 ± 14.4 years in migraine group and 44.5 ± 16.2 in the control group. Men with migraine had lower progesterone levels (0.2 nmoL/L, IQR 0.2) and a higher E2 to progesterone (E2/P) ratio (0.33, IQR 0.26) compared to healthy controls (0.5 nmoL/L, IQR 0.2, p < 0.001; 0.25, IQR 0.19, p < 0.02). Median E2 was 0.09 nmoL/L (IQR 0.03) in migraine patients and 0.12 nmoL/L (IQR 0.04) in controls (p = 0.07). There were no significant differences in testosterone, testosterone to E2 (T/E2) ratio, LH and FSH levels. CGRP serum levels did not differ between groups and showed no correlation with sex hormone levels. Subgroup analysis revealed no differences in hormone or CGRP levels between migraine patients with and without aura.DiscussionOur findings indicate higher progesterone levels and lower E2/P ratios in healthy men compared to those with migraine, suggesting a potential association between sex hormone profiles and migraine in men. These results warrant further investigation into the hormonal modulation of migraine beyond the female population.